The psychosocial predisposition effects in second language learning: motivational profile in Portuguese and Catalan samples - Figueiredo, Sandra (2018)
This present study examines the non-linguistic outcomes of second language learners groups and the data for this study were collected from an application of a tests battery – BAMA (motivational, affective and learning aspects assessment), developed in PhD research context. Were found differences between children and adolescents (305 Portuguese and 279 Catalan immigrant students), regarding motivation and attitudes in the second language learning and psychosocial adaptation contexts, taking into account their nationalities, mother tongues, age and gender. The children and female Catalan present the most favourable means, as predictors in the languages learning, what we can relate to previous research. In other hand, the Portuguese sample presents a distinct other profile, which could be compromising the language learning and psychosocial development.